A Cs0.32WO3 / (mt)-BiVO4 heterojunction and its preparation method and application
By forming a dual Z-type heterojunction structure of Cs0.32WO3/(m-t)-BiVO4 on BiVO4, the LSPR effect and photothermal effect of Cs0.32WO3 was used to solve the problem of insufficient response of existing BiVO4 photocatalysts to near-infrared light, and the Effects of efficient photocatalytic degradation under the full spectrum.
Patent Information
- Application Number
- CN202211064467.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-08-31
AI Technical Summary
The existing BiVO4 photocatalysts have low utilization of sunlight, and have disadvantages such as high recombination rate and fast recombination rate of photogenerated electron-hole pairs, so they cannot effectively utilize near-infrared light.
Using Cs0.32WO3/(m-t)-BiVO4 double Z-type heterojunction structure, the Z-type heterojunction was formed by granular Cs0.32WO3 loaded on the tetragonal phase t-BiVO4, and prepared by light selection deposition reaction method. Using the LSPR effect, small polaron transition and photothermal effect of Cs0.32WO3, the light response range is broadened and the photocatalytic activity is enhanced.
Under the full spectrum of ultraviolet-visible light-near-infrared light, the heterojunction of Cs0.32WO3/(m-t)-BiVO4 significantly improves the redox capacity and photocatalytic activity, and can effectively degrade antibiotics, phenol, salicylic acid, bisphenol A and fragrance. Organic pollutants such as soybean have broad-spectrum degradation performance and good circulation stability.
Smart Images

Figure HDA0003827618050000011 
Figure HDA0003827618050000012 
Figure HDA0003827618050000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional materials and relates to a Cs 0.32 WO3 / (mt)-BiVO4 heterojunction, preparation method and application thereof. Background Art
[0002] Monoclinic m-BiVO4 is a new type of bismuth-based semiconductor material with a layered structure, excellent carrier transmission channel and intrinsic visible light absorption, small bandgap, and green environmental protection. It is widely used in the field of photocatalysis. However, BiVO4 can only respond to ultraviolet-visible light, has low utilization of sunlight, and has disadvantages such as high recombination rate of photogenerated electron-hole pairs and fast recombination rate.
[0003] Document CN106745474B - A method for preparing a tungsten trioxide-bismuth vanadate heterojunction thin film electrode responsive to visible light discloses the use of bismuth nitrate and peroxyvanadic acid to react on the surface of a WO3 thin film to produce bismuth peroxyvanadate, repeated spin coating of a bismuth nitrate solution and a peroxyvanadic acid solution to obtain a WO3 thin film modified with bismuth peroxyvanadate, and a single heat treatment to obtain the WO3 / BiVO4 heterojunction thin film electrode. The thin film electrode has good visible light absorption performance and good stability. Since it does not involve a sintering process, it will not produce repeated and drastic stress changes, which will cause defects in the substrate WO3 thin film crystal. CN110042409A- Preparation method of tungsten oxide / bismuth vanadate heterojunction photoanode and self-powered photoelectrolysis water system, discloses a method of preparing a tungsten oxide film on fluorine-doped tin oxide conductive glass by a water bath method; using an electrochemical deposition method to deposit a bismuth vanadate film on the fluorine-doped tin oxide conductive glass formed with the tungsten oxide film, thereby obtaining the tungsten oxide / bismuth vanadate heterojunction photoanode, and using a xenon lamp cold light source (XD-300) equipped with an AM1.5G filter as a test light source, the tungsten oxide / bismuth vanadate heterojunction photoanode has extremely high photoelectrocatalytic performance. The heterojunction formed by WO3 and BiVO4 prepared in these documents only responds to visible light and sunlight, there are no defects in the WO3 thin film crystal, it does not respond to near-infrared light, and it is a two-phase heterojunction of WO3 and BiVO4, and there is no photothermal effect. Summary of the invention
[0004] The object of the present invention is to provide a Cs 0.32 WO3 / (mt)-BiVO4 heterojunction and its preparation method and application, the present invention Cs 0.32 The WO3 / (mt)-BiVO4 double Z-type heterojunction has enhanced redox ability under the full spectrum of ultraviolet-visible-near-infrared light, and the photothermal synergistic effect enhances the photocatalytic activity of the heterojunction.
[0005] The present invention is achieved through the following technical solutions:
[0006] A Cs 0.32 WO3 / (mt)-BiVO4 heterojunction, including decahedral monoclinic m-BiVO4 with exposed (010) crystal plane, tetragonal t-BiVO4 obtained by phase transformation of decahedral monoclinic m-BiVO4 with (110) crystal plane, and granular Cs supported on tetragonal t-BiVO4 0.32 WO3, decahedral monoclinic m-BiVO4 and tetragonal t-BiVO4 form a Z-type heterojunction; tetragonal t-BiVO4 and granular Cs 0.32 WO3 forms a Z-type heterojunction.
[0007] The Cs 0.32 A method for preparing a WO3 / (mt)-BiVO4 heterojunction comprises:
[0008] S1, Cs 0.32 WO3 crystal powder is dispersed in water and irradiated with ultraviolet light to obtain Cs 0.32 WO3 solution; dispersing decahedral monoclinic m-BiVO4 crystal powder with exposed (010) and (110) crystal faces in ethanol, and obtaining m-BiVO4 solution after irradiation with ultraviolet light;
[0009] S2, Cs 0.32 WO3 solution and m-BiVO4 solution are mixed and subjected to photoselective deposition reaction under ultraviolet light irradiation. The obtained product is washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0010] Preferably, in S1, the preparation method of the decahedral monoclinic m-BiVO4 crystal powder is:
[0011] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, and then adding NH4VO3 and stirring to form a precursor solution A;
[0012] Step 2: subjecting the precursor solution A to a hydrothermal reaction, washing and drying the precipitate obtained by the reaction, and obtaining a decahedral monoclinic m-BiVO4 crystal powder with exposed (010) and (110) crystal planes.
[0013] Preferably, in S1, the Cs 0.32 The preparation method of WO3 crystal powder is as follows:
[0014] Step 1, dissolving WCl6 and CsNO3 in anhydrous ethanol, adding acetic acid, stirring, to form precursor solution B;
[0015] Step 2: Solvent thermal reaction of precursor solution B, washing and drying the precipitate obtained by the reaction to obtain Cs 0.32 WO3 crystal powder.
[0016] Preferably, in S1, the ultraviolet light irradiation time is 30 to 40 minutes.
[0017] Preferably, in S2, the time of the light selective deposition reaction is 180 to 210 minutes.
[0018] Preferably, in S2, Cs 0.32 The molar ratio of WO3 and m-BiVO4 is (0.001~1.453):1.235.
[0019] The Cs 0.32 Application of WO3 / (mt)-BiVO4 heterojunction as photocatalyst in degradation of organic pollutants.
[0020] Preferably, the organic pollutant is an antibiotic, phenol, salicylic acid, bisphenol A or coumarin.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention 0.32 WO3 / (mt)-BiVO4 heterojunction, the monoclinic m-BiVO4 with exposed (010) crystal plane forms a Z-type heterojunction with the tetragonal t-BiVO4; the tetragonal t-BiVO4 and Cs 0.32 WO3 forms a second Z-type heterojunction, thus forming a double Z-type heterojunction structure. The double Z-type heterojunction is conducive to the effective separation and migration of photogenerated electrons and holes, making the composite photocatalyst have a higher redox ability. 0.32 The large number of free carriers and abundant oxygen vacancies in the special tunnel structure of WO3 have the LSPR effect and small polaron transition phenomenon, which broadens the light response range and enhances the absorption of near-infrared light, thus making Cs 0.32 WO3 / (mt)-BiVO4 heterojunction has photocatalytic properties under near-infrared light. 0.32 The photothermal effect of WO3 cooperates with the double Z-type heterojunction to increase the temperature of the reaction system and promote the degradation of organic pollutants, achieving excellent photocatalytic activity produced by the photothermal synergistic heterojunction under the full spectrum of ultraviolet-visible light-near infrared light.
[0023] The Cs provided by the present invention 0.32 WO3 / (mt)-BiVO4 heterojunction preparation method, during the light selective deposition reaction, the decahedral monoclinic m-BiVO4 with exposed (010) and (110) crystal planes is excited by ultraviolet light to produce h + and e- , and h + and e - Migrate to the (110) and (010) planes of m-BiVO4 respectively, and at the same time form a built-in electric field E1 from the (010) plane to the (110) plane on the (110) and (010) planes of the decahedral monoclinic phase m-BiVO4; the negatively charged Cs 0.32 WO3 (ζ=-15.2eV) nanoparticles are adsorbed on the positively charged (110) crystal plane of monoclinic m-BiVO4 under the action of electrostatic attraction, forming a decahedral monoclinic m-BiVO4 (110) crystal plane pointing to Cs 0.32 WO3 has a built-in electric field E2. At the same time, due to Cs 0.32 WO3 has a photothermal effect. After exposure to light, Cs 0.32 The temperature of WO3 increases, resulting in Cs 0.32 The (110) crystal plane of the monoclinic phase m-BiVO4 adsorbed by WO3 undergoes a phase transition to generate a tetragonal phase t-BiVO4. Under the action of the built-in electric field E1, the electrons on the conduction band of the tetragonal phase t-BiVO4 and the holes on the valence band of the monoclinic phase m-BiVO4 with the exposed (010) crystal plane will recombine at the interface, and the monoclinic phase m-BiVO4 with the exposed (010) crystal plane and the tetragonal phase t-BiVO4 will form a Z-type heterojunction; under the action of the built-in electric field E2, the holes on the valence band of the tetragonal phase t-BiVO4 and the Cs 0.32 The electrons in the WO3 conduction band recombine at the interface, and the tetragonal t-BiVO4 and Cs 0.32 WO3 forms a second Z-type heterostructure, and Cs 0.32 WO3 / (mt)-BiVO4 double Z-type heterojunction. That is, the present invention utilizes negatively charged Cs 0.32 The LSPR effect, small polaron transition and photothermal effect of WO3 lead to the 0.32 The (110) crystal plane of the monoclinic phase m-BiVO4 adsorbed by WO3 undergoes a phase transformation to generate a tetragonal phase t-BiVO4, exposing the (010) crystal plane of the monoclinic phase m-BiVO4 to form Cs 0.32 WO3 / (mt)-BiVO4 double Z-type heterojunction structure.
[0024] The present invention 0.32 WO3 / (mt)-BiVO4 double Z-type heterojunction, using Cs 0.32 The LSPR, small polaron transition and photothermal effect of WO3 oxygen vacancies synergize the heterojunction to make Cs 0.32The WO3 / (mt)-BiVO4 double Z-type heterojunction has a broad-spectrum degradation performance for antibiotics, phenol, salicylic acid, bisphenol A and coumarin under ultraviolet-visible-near infrared (200-2500nm) light, and has good application prospects in sewage purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The Cs prepared by the present invention 0.32 XRD pattern of WO3 / (mt)-BiVO4 heterojunction;
[0026] Figure 2 is a SEM image of a smooth decahedral monoclinic m-BiVO4 crystal prepared in Comparative Example 1;
[0027] Figure 3 The Cs prepared by the present invention 0.32 SEM image of WO3 / (mt)-BiVO4 heterojunction;
[0028] Figure 4 The Cs prepared by the present invention 0.32 HRTEM image of WO3 / (mt)-BiVO4 heterojunction;
[0029] Figure 5 The Cs prepared by the present invention 0.32 UV-visible diffuse reflectance image of WO3 / (mt)-BiVO4 heterojunction;
[0030] Figure 6 The Cs prepared by the present invention 0.32 EPR image of WO3 / (mt)-BiVO4 heterojunction;
[0031] Figure 7 The Cs prepared by the present invention 0.32 Degradation curve of WO3 / (mt)-BiVO4 heterojunction under visible light degradation of 40mg / LTC;
[0032] Figure 8 The Cs prepared by the present invention 0.32 Kinetic fitting curve of degradation of 40mg / LTC by WO3 / (mt)-BiVO4 heterojunction under visible light;
[0033] Fig. 9 The Cs prepared by the present invention 0.32 Degradation curve of WO3 / (mt)-BiVO4 heterojunction degrading 40mg / L TC under near-infrared light;
[0034] Fig.10 The Cs prepared by the present invention 0.32Kinetic fitting curve of WO3 / (mt)-BiVO4 heterojunction degradation of 40mg / L TC under near-infrared light;
[0035] Fig.11 This is a temperature change diagram of the smooth decahedral monoclinic m-BiVO4 crystal prepared in Comparative Example 1, taken by infrared temperature imaging during near-infrared light degradation;
[0036] Fig.12 The Cs prepared by the present invention 0.32 Temperature change of WO3 / (mt)-BiVO4 heterojunction during near-infrared photodegradation, as captured by infrared temperature imaging;
[0037] Fig.13 This is a temperature change diagram of 40mg / L TC solution taken by infrared temperature imaging during near-infrared light irradiation;
[0038] Fig.14 The Cs prepared by the present invention 0.32 TOC removal efficiency of WO3 / (mt)-BiVO4 heterojunction during visible light degradation;
[0039] Fig.15 The Cs prepared by the present invention 0.32 TOC removal efficiency of WO3 / (mt)-BiVO4 heterojunction during near-infrared photodegradation;
[0040] Fig.16 The Cs prepared by the present invention 0.32 Degradation curves of WO3 / (mt)-BiVO4 heterojunction under monochromatic light irradiation at 740nm, 850nm, 940nm, and 1100nm;
[0041] Fig.17 The Cs prepared by the present invention 0.32 Degradation curves of WO3 / (mt)-BiVO4 heterojunction under UV, Vis, NIR and simulated sunlight irradiation;
[0042] Fig.18 The Cs prepared by the present invention 0.32 Cyclic experiment of WO3 / (mt)-BiVO4 heterojunction degrading 40mg / L TC under visible light;
[0043] Fig.19 The Cs prepared by the present invention 0.32 Cyclic experiment of WO3 / (mt)-BiVO4 heterojunction degrading 40mg / L TC under near-infrared light;
[0044] Fig. 20 The Cs prepared by the present invention 0.32XRD pattern of WO3 / (mt)-BiVO4 heterojunction after cycling;
[0045] Fig.21 The Cs prepared by the present invention 0.32 Degradation efficiency of WO3 / (mt)-BiVO4 heterojunction for phenol, CIP, BHA, BPA and coumarin;
[0046] Fig. 22 The Cs prepared by the present invention 0.32 WO3 / (mt)-BiVO4 heterojunction active species capture experiment under visible light;
[0047] Fig.23 The Cs prepared by the present invention 0.32 Active species capture experiment under near-infrared light in WO3 / (mt)-BiVO4 heterojunction;
[0048] Fig.24 The Cs prepared by the present invention 0.32 Electrochemical impedance spectroscopy of WO3 / (mt)-BiVO4 heterojunction;
[0049] Fig.25 The Cs prepared by the present invention 0.32 Diagram of the photocatalytic mechanism of WO3 / (mt)-BiVO4 heterojunction. DETAILED DESCRIPTION
[0050] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0051] The Cs of the present invention 0.32 WO3 / (mt)-BiVO4 heterojunction, including decahedral monoclinic m-BiVO4 with exposed (010) crystal plane, tetragonal t-BiVO4 obtained by phase transformation of decahedral monoclinic m-BiVO4 with (110) crystal plane, and granular Cs supported on tetragonal t-BiVO4 0.32 WO3, decahedral monoclinic m-BiVO4 and tetragonal t-BiVO4 form a Z-type heterojunction; tetragonal t-BiVO4 and granular Cs 0.32 WO3 forms a Z-type heterojunction.
[0052] The Cs 0.32 The preparation method of WO3 / (mt)-BiVO4 heterojunction comprises the following steps:
[0053] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52 (at this pH, decahedral monoclinic m-BiVO4 crystals with exposed (010) and (110) crystal faces can be obtained), then adding NH4VO3, stirring, to form a precursor solution A;
[0054] Step 2, hydrothermally reacting the precursor solution A at 70-180° C. to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal with exposed (010) and (110) crystal faces;
[0055] Step 3, dissolve WCl6 and CsNO3 in anhydrous ethanol, stir until completely dissolved, the solution is light yellow, then add acetic acid, stir to form precursor solution B;
[0056] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave to perform a solvothermal reaction to obtain a blue precipitate, wash the blue precipitate with deionized water and anhydrous ethanol, and then vacuum dry to obtain a pure phase Cs 0.32 WO3 crystal powder;
[0057] Step 5: Cs 0.32 WO3 crystal powder is dispersed in water and irradiated with ultraviolet light to obtain Cs 0.32 WO3 solution; dispersing decahedral monoclinic m-BiVO4 crystal powder in ethanol, and irradiating with ultraviolet light to obtain m-BiVO4 solution;
[0058] Step 6: Cs 0.32 WO3 solution and m-BiVO4 solution are mixed and subjected to photoselective deposition reaction under ultraviolet light irradiation. The obtained product is washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0059] In step 5, the ultraviolet light irradiation time is 30 to 40 minutes; in step 6, the reaction time is 180 to 210 minutes.
[0060] In step 5, the added Cs 0.32 The molar ratio of WO3 and m-BiVO4 is (0.001~1.453):1.235.
[0061] Comparative Example 1
[0062] Step 1, dissolve 6mmoL Bi(NO3)3·5H2O in 35mL HNO3 solution with a concentration of 1mol / L at a uniform and slow speed under stirring conditions, stir for 30min until the solution is clarified, adjust the pH value of the solution to 0.52, then slowly add 6mmoL NH4VO3, stir for 150min, and form precursor solution A;
[0063] Step 2, after the precursor solution A is hydrothermally reacted at 70° C. for 15 h, the precipitate is collected, washed with water three times, and then washed with anhydrous ethanol three times to obtain a monoclinic m-BiVO4 (m-BVO) with a smooth decahedral morphology;
[0064] Comparative Example 2
[0065] Step 1, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min to form a precursor solution;
[0066] Step 2, the precursor solution is transferred into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and kept at 240° C. for 24 h to obtain a blue precipitate;
[0067] Step 3: Wash the blue precipitate with deionized water and anhydrous ethanol for three times, and then dry it in vacuum at 80°C for 12 hours to obtain nanoparticles of Cs 0.32 WO3(CWO) crystal.
[0068] Example 1
[0069] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0070] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0071] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0072] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0073] Step 5: 0.219 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0074] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4(15%-CWO / m-BVO / t-BVO) heterojunction.
[0075] Example 2
[0076] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0077] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0078] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0079] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0080] Step 5: 0.073 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0081] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4(5%-CWO / m-BVO / t-BVO) heterojunction.
[0082] Example 3
[0083] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0084] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0085] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0086] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0087] Step 5: 0.146 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0088] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32WO3 / (mt)-BiVO4(10%-CWO / m-BVO / t-BVO) heterojunction.
[0089] Example 4
[0090] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0091] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0092] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0093] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0094] Step 5: 0.291 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0095] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4(20%-CWO / m-BVO / t-BVO) heterojunction.
[0096] Example 5
[0097] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0098] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0099] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0100] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0101] Step 5: 0.001 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0102] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0103] Example 6
[0104] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0105] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0106] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0107] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0108] Step 5: 0.728 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0109] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0110] Example 7
[0111] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0112] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0113] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0114] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0115] Step 5: 1.311 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0116] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0117] Example 8
[0118] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0119] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0120] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0121] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0122] Step 5: 1.453 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0123] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0124] Example 9
[0125] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0126] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0127] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0128] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0129] Step 5: 0.219 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 35 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 35min, a monoclinic m-BiVO4 solution was obtained;
[0130] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0131] Example 10
[0132] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0133] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0134] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0135] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0136] Step 5: 0.219 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 40 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 40min, a monoclinic m-BiVO4 solution was obtained;
[0137] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 180 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0138] Embodiment 11
[0139] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0140] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0141] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0142] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0143] Step 5: 0.219 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0144] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 190 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0145] Example 12
[0146] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0147] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0148] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0149] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0150] Step 5: 0.219 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0151] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 200 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0152] Example 13
[0153] Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH of the solution to 0.52, then adding NH4VO3, stirring for 150 min, to form a precursor solution A;
[0154] Step 2, hydrothermally reacting the precursor solution A at 70° C. for 15 h to obtain a yellow precipitate, washing the yellow precipitate with deionized water and anhydrous ethanol, and drying to obtain a smooth decahedral monoclinic m-BiVO4 crystal;
[0155] Step 3, dissolve 1.13mmoL WCl6 and 0.57mmoL CsNO3 in 80mL anhydrous ethanol, stir for 5h until completely dissolved, the solution is light yellow, then add 20mL acetic acid, stir for 30min, to form precursor solution B;
[0156] Step 4: transfer the precursor solution B into a polytetrafluoroethylene-lined autoclave at a filling rate of 80%, and keep it at 240°C for 24 hours to obtain a blue precipitate. The blue precipitate is washed with deionized water and anhydrous ethanol for 3 times, and then vacuum dried at 80°C for 12 hours to obtain a pure phase Cs 0.32 WO3 crystal;
[0157] Step 5: 0.219 mmol Cs 0.32 WO3 powder was dispersed in 25 mL of water and irradiated with UV light for 30 min to obtain Cs 0.32 WO3 solution; 1.235mmol of monoclinic m-BiVO4 powder was dispersed in 35mL of ethanol, and after irradiation with ultraviolet light for 30min, a monoclinic m-BiVO4 solution was obtained;
[0158] Step 6: Cs 0.32 The WO3 solution and the monoclinic m-BiVO4 solution were mixed and reacted under ultraviolet light for 210 min. The obtained product was washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
[0159] Figure 1 The Cs prepared in Comparative Example 1, Comparative Example 2 and Examples 1-4 0.32 The XRD pattern of WO3 / (mt)-BiVO4 heterojunction shows that the diffraction peaks at 18.67°, 28.95° and 30.55° correspond to the (110), (121) and (010) crystal planes of the monoclinic scheelite phase BiVO4 (m-BiVO4) standard card (JCPDS No.14-0688); the diffraction peaks at 2θ=18.32°, 24.37°, 32.68°, 39.53° and 48.40° belong to the (101), (200), (112), (301) and (312) crystal planes of the tetragonal zircon phase BiVO4 (t-BiVO4) standard card (JCPDS No.14-0133); the diffraction peak appearing at a diffraction angle of 27.78° corresponds to the hexagonal phase Cs 0.32 The (200) crystal plane of the standard card of WO3 (JCPDS No.83-1334). All XRD parameters of the composite material show that the prepared m-BiVO4 0.32 After WO3, m-BiVO4 transforms into (mt)-BiVO4 mixed crystal phase, and Cs 0.32 The coexistence of WO3, m-BiVO4 and t-BiVO4 phases indicates that Cs 0.32 WO3 / (mt)-BiVO4 heterojunction, and no new diffraction peaks were observed in the sample, indicating that no impurities were formed during the preparation process.
[0160] Figure 2 This is a SEM image of the monoclinic m-BiVO4 crystal with smooth decahedral morphology prepared in Comparative Example 1. The BiVO4 prepared hydrothermally has smooth, flat and relatively sharp edges and is a decahedron with exposed (010) and (110) crystal planes. Figure 3 is the Cs prepared in Example 1 0.32 SEM image of WO3 / (mt)-BiVO4. It can be seen from the image that nanoparticles of Cs 0.32 WO3 forms a cluster morphology, which is tightly loaded on the (110) crystal plane of the decahedral monoclinic phase m-BiVO4, exposing the (010) crystal plane of m-BiVO4. Figure 4 is the Cs prepared in Example 1 0.32 HRTEM image of WO3 / (mt)-BiVO4, showing different lattice fringes. The lattice fringes with spacing of 0.205nm, 0.245nm, 0.321nm and 0.380nm correspond to Cs 0.32The (212), (202), (200) and (002) lattice planes of WO3; 0.228nm and 0.365nm correspond to the (301) and (200) lattice planes of tetragonal t-BiVO4; and the lattice fringe spacing of 0.308nm corresponds to the (121) lattice plane of monoclinic m-BiVO4. HRTEM image results further show that Cs 0.32 WO3, tetragonal t-BiVO4 and monoclinic m-BiVO4 coexist, and Cs 0.32 WO3 forms an interface with the tetragonal phase t-BiVO4.
[0161] Figure 5 The Cs prepared in Comparative Example 1, Comparative Example 2 and Examples 1-4 0.32 UV-visible diffuse reflectance image of WO3 / (mt)-BiVO4 heterojunction. In the UV-visible diffuse reflectance image, Cs 0.32 WO3 has light absorption in the range of 200-2200nm. 0.32 The small polaron transition phenomenon and LSPR effect of WO3 make it show strong absorption in the near-infrared light range. However, the monoclinic phase m-BiVO4 shows significantly enhanced light absorption in the ultraviolet-visible light range of 200-800nm. 0.32 Compared with the monoclinic m-BiVO4, the WO3 / (mt)-BiVO4 heterojunction has enhanced absorption in the near-infrared range of 800-2200nm and has full-spectrum absorption in the ultraviolet-visible-near-infrared range. This is due to the use of Cs 0.32 The small polaron transition phenomenon in WO3 absorbs near-infrared light during the transition process, and Cs 0.32 WO3 also has LSPR effect, which further enhances light absorption and heterojunction formation. Due to the synergistic effect of small polaron transition, LSPR effect and heterojunction, Cs 0.32 WO3 / (mt)-BiVO4 shows significantly enhanced visible-near-infrared light absorption and improved solar energy utilization. Figure 6 The Cs prepared in Comparative Example 1, Comparative Example 2 and Example 1 0.32 EPR spectrum of WO3 / (mt)-BiVO4 heterojunction. It can be seen from the figure that m-BiVO4 has no identifiable EPR signal, indicating that there are no oxygen vacancies or the concentration of oxygen vacancies is low in m-BiVO4. When the g value of the EPR signal appears around 2.003, it is attributed to the presence of defects. When g = 2.003, Cs 0.32 Both WO3 and 15%-CWO / m-BVO / t-BVO show a strong oxygen vacancy signal, indicating that 15%-CWO / m-BVO / t-BVO contains Cs 0.32WO3, and because Cs 0.32 WO3 has abundant oxygen vacancies, which leads to the presence of a large number of oxygen vacancies in the composite sample. At the same time, the abundant oxygen vacancies will cause a unique LSPR effect and also cause the composite sample to produce certain absorption in the near-infrared light region. Figure 7 The Cs prepared in Comparative Example 1, Comparative Example 2 and Examples 1-4 0.32 Degradation curve of WO3 / (mt)-BiVO4 double Z-type heterojunction degrading 40mg / L tetracycline (TC) under visible light. Figure 8 The Cs prepared in Comparative Example 1, Comparative Example 2 and Examples 1-4 0.32 Kinetic fitting curve of degradation of 40mg / L TC by WO3 / (mt)-BiVO4 double Z-type heterojunction under visible light. The reaction was first carried out in the dark for 30 minutes, and after reaching the adsorption-desorption equilibrium, the light reaction was carried out. It can be seen from the figure that in the absence of any photocatalyst, the self-degradation efficiency of TC can be ignored. Therefore, the removal of TC comes from the photodegradation of the photocatalyst. Within 180 minutes of visible light irradiation, m-BiVO4 only degraded 46.28% of TC, and the corresponding degradation rate was 0.00358min -1 , Cs 0.32 The degradation rate of WO3 to TC is 53.26%, and its degradation rate is 0.00495min -1 , double Z-type heterojunction 5%-CWO / m-BVO / t-BVO, 10%-CWO / m-BVO /
[0162] t-BVO, 15%-CWO / m-BVO / t-BVO and 20%-CWO / m-BVO / t-BVO can degrade 85.40%, 88.14%, 90.57% and 87.19% of TC, respectively, and their degradation rates are 0.0116 min -1 、0.0127min -1 、0.0138min -1 and 0.0124min -1 Among them, the 15%-CWO / m-BVO / t-BVO composite sample has the best degradation rate for TC, which is 1.96 times that of m-BiVO4 and 1.96 times that of Cs 0.32 The degradation rate of Cs 0.32 The degradation rate of WO3 is 2.79 times higher than that of WO3. This indicates that the double Z-type heterojunction increases the degradation rate of Cs 0.32 Photocatalytic performance of WO3 / (mt)-BiVO4 double Z-type heterojunction.
[0163] Fig. 9The Cs prepared in Comparative Example 1, Comparative Example 2 and Examples 1-4 0.32 Degradation curve of 40mg / L TC degraded by WO3 / (mt)-BiVO4 double Z-type heterojunction under near-infrared light. After 30 minutes of dark reaction, the adsorption-desorption equilibrium was reached, and then the light reaction was carried out. It can be seen from the figure that in the absence of any photocatalyst, the self-degradation efficiency of TC can be ignored. Therefore, the removal of TC comes from the photodegradation of the photocatalyst. After 180 minutes of near-infrared light irradiation, the m-BiVO4 and Cs 0.32 The degradation rates of TC by WO3, 5%-CWO / m-BVO / t-BVO, 10%-CWO / m-BVO / t-BVO, 15%-CWO / m-BVO / t-BVO and 20%-CWO / m-BVO / t-BVO were 14.22%, 55.72%, 86.72%, 87.99%, 92.08% and 89.29%, respectively. Fig.10 As shown, m-BiVO4, Cs 0.32 The apparent rate constants of WO3, 5%-CWO / m-BVO / t-BVO, 10%-CWO / m-BVO / t-BVO, 15%-CWO / m-BVO / t-BVO and 20%-CWO / m-BVO / t-BVO are 0.00105min, respectively. -1 、0.00527min -1 、0.01208min -1 、0.01261min -1 、0.01480min -1 and 0.01345min -1 The photocatalytic activity of 15%-CWO / m-BVO / t-BVO exceeds that of m-BiVO4 by about 14.10 times. This is due to the 0.32 The LSPR effect of WO3, small polaron transition and double Z-type heterojunction enhance the absorption of near-infrared light and accelerate the separation of photogenerated electrons and holes, thereby greatly improving the photocatalytic activity.
[0164] Fig.11 This is a temperature change diagram of the smooth decahedral monoclinic m-BiVO4 crystal prepared in Comparative Example 1, taken by infrared temperature imaging during near-infrared light degradation. Fig.12 The Cs prepared by the present invention 0.32 Temperature variation of WO3 / (mt)-BiVO4 double Z-type heterojunction captured by infrared temperature imaging during near-infrared photodegradation. Fig.13This is a temperature change diagram of 40mg / L TC solution taken by infrared temperature imaging during near-infrared light irradiation. During the entire degradation process of TC by m-BiVO4 and 15%-CWO / m-BVO / t-BVO under near-infrared light (800-2500nm), the temperature change of pure TC solution caused by near-infrared light is taken into account. Therefore, after removing the part where the temperature of pure TC solution increases due to near-infrared light, the actual temperature contribution of m-BiVO4 and 15%-CWO / m-BVO / t-BVO to the degradation process of TC is about 1°C and 24.9°C respectively. Therefore, it is shown that Cs 0.32 The WO3 / (mt)-BiVO4 double Z-type heterojunction has an excellent photothermal effect in the liquid phase, and the thermal effect is beneficial to the charge transfer in the photocatalytic process. This photothermal effect cooperates with the double Z-type heterojunction to enhance the heterojunction redox ability, increase the reaction activation energy, accelerate the charge transfer rate and reaction rate in the photocatalytic process, and thus significantly improve the photocatalytic activity.
[0165] Fig.14 The Cs prepared in Comparative Example 1, Comparative Example 2 and Example 1 0.32 Organic carbon removal rate (TOC) of WO3 / (mt)-BiVO4 heterojunction during visible light degradation. From the TOC test results, it can be seen that the TOC removal rate of the original 40mg / L TC solution gradually increases with the extension of the illumination time, indicating that TC gradually decomposes into H2O and CO2. After 180min of visible light irradiation, the TOC removal rate increases from 28.61% (m-BiVO4) and 38.94% (Cs 0.32 WO3) significantly increased to 73.79% (15%-CWO / m-BVO / t-BVO). Under near-infrared light irradiation ( Fig.15 ), the TOC removal rate of 15%-CWO / m-BVO / t-BVO for TC reached 75.03%, which was also higher than that of m-BiVO4 (12.20%) and Cs 0.32 WO3 (34.93%), indicating that Cs 0.32 The WO3 / (mt)-BiVO4 double Z-type heterojunction has good mineralization ability.
[0166] Fig.16 is the Cs prepared in Example 1 0.32Degradation curves of WO3 / (mt)-BiVO4 heterojunction at 740nm, 850nm, 940nm and 1100nm under monochromatic light irradiation. After 180min of illumination, the degradation rates of TC (40mg / L TC solution) degraded by 15%-CWO / m-BVO / t-BVO were 77.66% under 740nm monochromatic light irradiation, 79.78% under 850nm monochromatic light irradiation, 76.57% under 940nm monochromatic light irradiation and 72.60% under 1100nm monochromatic light irradiation. It was confirmed that due to the small polaron transition and LSPR effect, the prepared 15%-CWO / m-BVO / t-BVO photocatalyst has full-spectrum driven photocatalytic activity. Next, the photocatalytic performance of Example 1 under different illumination conditions was investigated ( Fig.17 The degradation rate under UV (200-400nm) light irradiation is 90.62%, the degradation rate under Vis (400-800nm) light irradiation is 90.57%, the degradation rate under NIR (800-2500nm) light irradiation is 92.08%, and the degradation rate under simulated sunlight (200-2500nm) light irradiation is 86.69%. The double Z-type heterojunction prepared in Example 1 all exhibits excellent photocatalytic degradation ability. Based on the above results, the Cs prepared in the present invention 0.32 The WO3 / (mt)-BiVO4 double Z-type heterojunction exhibits superior photocatalytic activity across the entire solar spectrum.
[0167] Fig.18 is the Cs prepared in Example 1 0.32 Cyclic experiment of WO3 / (mt)-BiVO4 double Z-type heterojunction degrading 40mg / L TC under visible light. Under visible light irradiation, after the first cycle, the degradation rate of TC by 15%-CWO / m-BVO / t-BVO was 90.57%, after the second cycle, the degradation rate of TC by 15%-CWO / m-BVO / t-BVO reached 89.08%, after the third cycle, the degradation rate of TC by 15%-CWO / m-BVO / t-BVO reached 87.39%, and finally after the fourth cycle, the degradation rate of TC by 15%-CWO / m-BVO / t-BVO reached 85.39%. Fig.19As shown, under near-infrared light irradiation, after the first cycle, the degradation rate of TC by 15%-CWO / m-BVO / t-BVO was 92.08%, after the second cycle, the degradation rate of TC by 15%-CWO / m-BVO / t-BVO reached 89.65%, after the third cycle, the degradation rate of TC by 15%-CWO / m-BVO / t-BVO reached 87.37%, and after the fourth cycle, the degradation rate of TC by 15%-CWO / m-BVO / t-BVO reached 85.64%. With the increase of the number of cycles, there was only a 5.18% decrease after the cyclic reaction under visible light conditions, and only a 6.44% decrease after the cyclic reaction under near-infrared light. This situation is mainly caused by the partial mass loss of the photocatalyst before and after the cycle. After four cycles of experiments, Cs 0.32 The XRD pattern of the WO3 / (mt)-BiVO4 double Z-type heterojunction remains basically unchanged ( Fig. 20 ), maintaining a stable phase structure. The above results prove that the synthesized photocatalyst has a high cycle stability, indicating that the heterojunction can transport carriers faster, and the existing photothermal effect cooperates with the heterojunction to promote the occurrence of degradation reactions.
[0168] Fig.21 is the Cs prepared in Example 1 0.32 Degradation efficiency of WO3 / (mt)-BiVO4 double Z-type heterojunction for phenol, CIP, BHA, BPA and coumarin (20 mg / L organic solution). Under visible light irradiation for 180 min, the degradation rates of double Z-type heterojunction for CIP, BHA, phenol, BPA and coumarin were 72.74%, 66.68%, 69.83%, 54.44% and 61.36%, respectively; under near-infrared light irradiation for 180 min, the maximum degradation rates of double Z-type heterojunction for ciprofloxacin (CIP), salicylic acid (BHA), phenol, bisphenol A (BPA) and coumarin were 71.20%, 46.10%, 42.18%, 48.44% and 53.74%, respectively. This shows that the prepared Cs 0.32 The WO3 / (mt)-BiVO4 double Z-type heterojunction can degrade different types of pollutants to varying degrees and has high broad spectrum and application value.
[0169] Fig. 22 The Cs prepared by the present invention 0.32 WO3 / (mt)-BiVO4 double Z-type heterojunction active species capture experiment under visible light. In the photocatalytic degradation system, p-benzoquinone (BQ), sodium oxalate (Na2C2O4) and tert-butyl alcohol (TBA) were added as O2 - 、h +As can be seen from the figure, under visible light irradiation, the photocatalytic performance of BQ, Na2C2O4 and TBA decreased by 9.46%, 50.64% and 16.63% respectively. This indicates that during the degradation reaction under visible light conditions, h + is the main active species, followed by ·OH and ·O2 - Under near-infrared light irradiation conditions ( Fig.23 ), after adding BQ, Na2C2O4 and TBA, the degradation ability of the photocatalyst decreased by 7.29%, 40.41% and 10.68%, respectively. + is the main active species in the degradation process, while ·OH plays a minor role in the degradation process, and the least active species is ·O2 - .
[0170] Fig.24 The Cs prepared in Comparative Example 1, Comparative Example 2 and Examples 1-4 0.32 Electrochemical impedance diagram of WO3 / (mt)-BiVO4 heterojunction. As shown in the figure, the Nyquist arc radius of 15%-CWO / m-BVO / t-BVO is significantly smaller than that of m-BiVO4 and Cs 0.32 WO3, 5%-CWO / m-BVO / t-BVO, 10%-CWO / m-BVO / t-BVO and 20%-CWO / m-BVO / t-BVO, indicating that 15%-CWO / m-BVO / t-BVO is conducive to the transfer of charges.
[0171] Fig.25 The Cs prepared by the present invention 0.32 WO3 / (mt)-BiVO4 double Z-type heterojunction photocatalytic mechanism diagram. As a heterojunction photocatalyst, Cs 0.32 WO3, t-BiVO4 and m-BiVO4 with exposed (010) crystal facets generate photogenerated electrons and holes in response to light. Due to the built-in electric field E1 formed at the interface between t-BiVO4 and m-BiVO4 with exposed (010) crystal facets, the photogenerated electrons in the conduction band of t-BiVO4 and the photogenerated holes in the valence band of m-BiVO4 with exposed (010) crystal facets recombine at the interface, retaining the photogenerated electrons in the conduction band of m-BiVO4 with exposed (010) crystal facets and the photogenerated holes in the valence band of t-BiVO4. The photogenerated electrons in the conduction band of m-BiVO4 with exposed (010) crystal facets reduce O2 to ·O2 - Free radicals degrade organic pollutant molecules; Cs 0.32 Photogenerated electrons in the conduction band of WO3 in t-BiVO4 and Cs 0.32Under the action of the built-in electric field E2 formed at the interface of WO3, it recombine with the photogenerated holes in the valence band of t-BiVO4 at the interface, retaining the Cs 0.32 The photogenerated holes in the WO3 valence band directly degrade organic pollutants. 0.32 The valence band potential of WO3 is 2.82eV, OH - The redox potential of OH is 1.99 eV, which can react with H2O or OH - The reaction generates ·OH which participates in the reduction reaction of pollutants and directly degrades organic pollutants. 0.32 When the electrons bound by oxygen vacancies in WO3 are irradiated by visible light (>500nm) and near-infrared light, the LSPR effect of oxygen vacancies induces electrons to move from their W 5+ The site escapes, and then the original W 5+ Oxidized to W 6+ (W 5+ +hv(Vis or NIR)→W 6+ +e - ). Some of the escaped hot electrons go to the adjacent W position, thus forming a new W 5+ bit, hv+W occurs 5+ (A)+W 6+ (B) → W 6+ (A)+W 5+ (B)+E phonon reacts and radiates energy in the form of phonons, making Cs 0.32 The WO3 / (mt)-BiVO4 double Z-type heterojunction has an excellent photothermal effect in the liquid phase. The temperature of the heating system increases by 24.9°C, which accelerates the degradation reaction. The remaining escaped hot electrons are captured by the dissolved oxygen O2 in the solution to form ·O2 - , and then generate ·OH, ·OOH and 1 O2(e - +O2 → ·O2 - +H + →·OOH→→·OH,·O2 - + OH → 1 O2+OH - ), W 6+ Site and OH - Then react and return W 5+ (W 6+ +OH - →W 5+ +·OH), realizing the full photocatalytic cycle. The active components include ·OH, ·OOH and 1 O2, which has sufficient energy for the oxidation of organic pollutants (·O2 - ,·OH, 1O2+organic pollutant→Degradation of organic pollutant). In addition, the photocatalytic reaction system has (e - +O2 → ·O2 - +H + →·OOH→→·OH,·O2 - + OH → 1 O2+OH - , W 6+ +OH - →W 5+ +·OH) reaction, the photogenerated electrons on the m-BiVO4 conduction band exposed on the (010) crystal surface reduce O2 to form ·O2 - , will also follow ·O2 - + OH → 1 O2+OH - and W 6+ +OH - →W 5+ +·OH reacts, consuming ·O2 - , resulting in the degradation reaction of visible light and near-infrared light, the photocatalytic system h + is the main active species in the degradation process, while ·OH plays a minor role in the degradation process, and the least active species is ·O2 - , the results are similar to Fig. 22 and Fig.23 The active species capture experiments under visible light and near-infrared light are consistent.
[0172] LSPR effect of oxygen vacancies, Cs 0.32 The photothermal effect of WO3 small polaron transition and the double Z-shaped heterojunction structure make Cs 0.32 The WO3 / (mt)-BiVO4 double Z-type heterojunction photothermal synergistic effect has a broad-spectrum and stable degradation performance for organic pollutants such as antibiotics, phenol, salicylic acid, bisphenol A and coumarin under ultraviolet-visible light and near-infrared light.
[0173] The above contents are further detailed descriptions of the present invention in combination with specific preferred implementation modes, and are not all or the only implementation modes. Any equivalent changes made to the technical solutions of the present invention by ordinary technicians in this field after reading the specification of the present invention are covered by the claims of the present invention.
Claims
1. A Cs 0.32 WO3 / (mt)-BiVO4 heterojunction, characterized by: The present invention comprises a decahedral monoclinic m-BiVO4 with exposed (010) crystal plane, a tetragonal t-BiVO4 obtained by phase transformation of the (110) crystal plane of the decahedral monoclinic m-BiVO4, and a granular Cs supported on the tetragonal t-BiVO4. 0.32 WO3, decahedral monoclinic m-BiVO4 and tetragonal t-BiVO4 form a Z-type heterojunction; tetragonal t-BiVO4 and granular Cs 0.32 WO3 forms a Z-type heterojunction.
2. Cs according to claim 1 0.32 The method for preparing a WO3 / (mt)-BiVO4 heterojunction is characterized in that: include: S1, Cs 0.32 WO3 crystal powder is dispersed in water and irradiated with ultraviolet light to obtain Cs 0.32 WO3 solution; dispersing decahedral monoclinic m-BiVO4 crystal powder with exposed (010) and (110) crystal faces in ethanol, and obtaining m-BiVO4 solution after irradiation with ultraviolet light; S2, Cs 0.32 WO3 solution and m-BiVO4 solution are mixed and subjected to photoselective deposition reaction under ultraviolet light irradiation. The obtained product is washed and dried to obtain Cs 0.32 WO3 / (mt)-BiVO4 heterojunction.
3. Cs according to claim 2 0.32 The method for preparing a WO3 / (mt)-BiVO4 heterojunction is characterized in that: In S1, the preparation method of the decahedral monoclinic m-BiVO4 crystal powder is: Step 1, dissolving Bi(NO3)3·5H2O in a dilute HNO3 solution, stirring until clear, adjusting the pH to 0.52, and then adding NH4VO3 and stirring to form a precursor solution A; Step 2: subjecting the precursor solution A to a hydrothermal reaction, washing and drying the precipitate obtained by the reaction, and obtaining a decahedral monoclinic m-BiVO4 crystal powder with exposed (010) and (110) crystal planes.
4. Cs according to claim 2 0.32 The method for preparing a WO3 / (mt)-BiVO4 heterojunction is characterized in that: In S1, the Cs 0.32 The preparation method of WO3 crystal powder is as follows: Step 1, dissolving WCl6 and CsNO3 in anhydrous ethanol, adding acetic acid, stirring, to form precursor solution B; Step 2: Solvent thermal reaction of precursor solution B, washing and drying the precipitate obtained by the reaction to obtain Cs 0.32 WO3 crystal powder.
5. Cs according to claim 2 0.32 The method for preparing a WO3 / (mt)-BiVO4 heterojunction is characterized in that: In S1, the ultraviolet light irradiation time is 30 to 40 minutes.
6. Cs according to claim 2 0.32 The method for preparing a WO3 / (mt)-BiVO4 heterojunction is characterized in that: In S2, the time of the light-selective deposition reaction is 180 to 210 minutes.
7. Cs according to claim 2 0.32 The method for preparing a WO3 / (mt)-BiVO4 heterojunction is characterized in that: In S2, Cs 0.32 The molar ratio of WO3 and m-BiVO4 is (0.001~1.453):1.
235.
8. Cs according to claim 1 0.32 Application of WO3 / (mt)-BiVO4 heterojunction as photocatalyst in degradation of organic pollutants.
9. The use according to claim 8, characterized in that: The organic pollutants are antibiotics, phenol, salicylic acid, bisphenol A or coumarin.
Citation Information
Patent Citations
Method for fabricating visible light responsive tungsten trioxide-bismuth vanadate heterojunction thin film electrodes
CN106745474B
Preparation method of tungsten oxide / bismuth vanadate heterojunction photoanode and self-powered photoelectrolysis water system
CN110042409A